Pelatihan Penggunaan Fitur-Fitur Baru Driver Bagi Anggota Brother Maxim Khatulistiwa, Kota Pontianak - Wandi Sujatmiko (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to evaluate the effectiveness of training on the use of new features for Brother Maxim members in Pontianak City. These new features are designed to improve the efficiency and quality of service provided by Brother Maxim drivers to customers. The research method involves conducting intensive training, measuring improvements in skills and understanding of the use of new features, as well as evaluating their impact on customer satisfaction and operational efficiency. It is hoped that the results of this research will provide useful recommendations for Brother Maxim management in improving service and customer satisfaction through the use of new features.